2018
DOI: 10.1155/2018/4178021
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Stimulates Bone Marrow Mesenchymal Stem Cell Differentiation through an Estrogen Receptor-Mediated Pathway

Abstract: Objectives The present study aimed to investigate the overall effect of quercetin on mouse bone marrow mesenchymal stem cell (BMSC) proliferation and osteogenic differentiation in vitro. Materials and Methods BMSCs were treated with different concentrations of quercetin for 6 days. The effects of quercetin on cell proliferation were assessed at predetermined times using Cell Counting Kit-8 (CCK-8) assay. The cells were then treated with quercetin, estrogen, or an estrogen receptor (ER) antagonist (which was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…20 Another study showed that quercetin enhanced bone marrow MSC proliferation and osteogenic differentiation. 21 This indicates that C. olitorius has the potential to increase stem cell proliferation by its rich polyphenolic content, which might be supportive for stem cell differentiation and better for mimicking in vivo structures and further tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…20 Another study showed that quercetin enhanced bone marrow MSC proliferation and osteogenic differentiation. 21 This indicates that C. olitorius has the potential to increase stem cell proliferation by its rich polyphenolic content, which might be supportive for stem cell differentiation and better for mimicking in vivo structures and further tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…In spleen and bone marrow, the expression was increased significantly, while in the liver, it decreased significantly (Figure 9). Modulation of Higd2a expression might be related to the effects of quercetin on cellular proliferation in promoting healthy bone marrow mesenchymal stem cell (BMSC) proliferation [66,67]. BMSCs cultured and treated with quercetin (0.1-5 µM and 1-10 µM for the isolation of mouse and rat tissues, respectively) significantly stimulated cells [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of Higd2a expression might be related to the effects of quercetin on cellular proliferation in promoting healthy bone marrow mesenchymal stem cell (BMSC) proliferation [66,67]. BMSCs cultured and treated with quercetin (0.1-5 µM and 1-10 µM for the isolation of mouse and rat tissues, respectively) significantly stimulated cells [66,67]. On the other hand, quercetin could have antiproliferative effects [68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin and luteolin promoted human hematopoietic stem cell differentiation [141] and were confirmed safe for developing vertebrates in terms of neurobehavior [142]. [138] into bone cells Increased Rat BM-MSCs cultures [129], mice BM-MSC cultures [130] Decreased Human BM cell cultures [133] into β-cells Increased Rat BM-MSCs cultures [131] into hepatic cells Increased Human BM cell cultures [134] into fat tissue cells Increased Human BM cell cultures [133] Proinflammatory cytokines Decreased Rat model of spinal cord injury [132] Anti-inflammatory cytokines Increased Rat model of spinal cord injury [132] Angiogenic factor secretion Increased Rat BM-MSC cultures [135] BDNF secretion Increased Human embryonic NSCs culture [138] BDNF: Brain-derived neurotrophic factor, BM: Bone marrow, hHSC: Human hematopoietic stem cells, MSC: Mesenchymal stem cells, NSC: Neural stem cells, hPSCs: Human pluripotent stem cells.…”
Section: Past and Future Perspectivesmentioning
confidence: 96%
“…Quercetin has multiple effects (Table 4). It enhanced the differentiation of BM-MSCs into bone cells in rat [129] and mice models [130]. In vitro, quercetin promoted the differentiation of BM-MSCs into β-cells with increased insulin secretion [131].…”
Section: Past and Future Perspectivesmentioning
confidence: 99%